NUMERICAL-RESEARCH ANALYSIS OF THE WORK OF COMPRESSED COMPOSITE THIN-WALLED ELEMENTS - Różyło, Patryk; Wysmulski, Paweł; Falkowicz, Katarzyna (Journal of Technology and Exploitation in Mechanical Engineering _ARCHIVE ISSUES, 2016)
Thin-walled, composite elements subjected to axial compression were the subject of conducted research. The samples were articulately propped against the edges of their cross-section. The scope of the research included a numerical analysis and experimental verification of both critical and weakly postcritical states. Numerical investigations were carried out in the elastic field, allowing for steady work of thin-walled structures until they reached the point of stability loss, with the simultaneous determination of critical forces values. For numerical calculations software ABAQUS® was used. The main issue of the research was to determine a convergence of the results obtained by numerical and experimental examination, in the range of operational allowable loads.